Graduate profiles of Dentistry programs in Peru - Velasco Luna , Luis Angel (2025)
Objective: To identify the competencies declared in the graduate profiles of Dentistry and Stomatology programs in Peru. Materials and methods: A descriptive, cross-sectional, observational study was conducted. The study population comprised Dentistry and Stomatology programs listed in TUNI, the official platform of the National Superintendency of Higher University Education (SUNEDU). Programs with no publicly available graduate profile information on their institutional websites were excluded. Competencies were extracted, categorized, and systematized based on reference frameworks from the Peruvian Dental Association and the Ministry of Health. Results: The most frequent competencies in the graduate profiles were clinical and research-related (85.19%; n = 23), followed by ethical-moral competencies (70.37%; n = 19). Empathy was the least frequently reported competency (11.11%; n = 3). Conclusion: Across public and private universities, clinical and research competencies were the most prevalent in the graduate profiles of Dentistry and Stomatology programs in Peru.